Optimalisasi Pemberdayaan Pelaku Umkm Desa Margaluyu Melalui Edukasi Marketing Digital - Ika Widiastuti; Sri Mulyono (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
This article discusses optimizing the empowerment of Micro, Small and Medium Enterprises (UMKM) in Margaluyu Village through digital marketing education. Margaluyu Village is a village rich in UMKM potential. The challenge is in marketing the products of the Margaluyu Village community so that they can run effectively. Therefore, it is important to provide education in digital marketing to increase the competitiveness and sustainability of UMKM. The digital marketing education introduced covers various aspects of online marketing, such as Social Media Marketing (Twitter, WhatsApp, Instagram, Facebook, Tiktok), Video Marketing and the largest marketplace in Indonesia (Tokopedia, Shopee, Bukalapak, Lazada, Blibli). Honey producers as UMKM are given training on utilizing digital platforms to expand market reach, increase brand visibility and increase sales. Apart from that, education is also needed about creating interesting content in accordance with consumer behavior analysis and market trends. This article concludes that digital marketing education can play an important role in empowerment, sales, increasing competitiveness with honey producers in other regions and contributing to village economic growth.